Electronic Word: Information Communicative Approach to Technologization of the Word - (:unkn) unknown (TURKISH LIBRARIANS ASSOC, 2016)
In this study, technologization of the word is considered in the context of information communicative approach. The content of the research is to reveal the transformation stages of the word and impact of each stage on information and communication in the transforming World. The study aims to determine the electronic word in terms of information and communication and to emphasize its importance. Perspective of the study is the electronic word and its methodology is based on the examination of living spaces of the word through a descriptive method. In the concept of this study, the findings were examined in an analytical manner after searching the literature on electronic word. According to the findings of the study results, the electronic word appears as a result of the processes and technologies that were supplied by each other. In essence, the word has emerged the phenomenon of information transmission and information retrieval. Furthermore, the electronic word improves in the parallel of these phenomena. It is estimated that the electronic word brings a new dynamism to information communication. As a result; transforming of the electronic word means that the interactive information flows. Through the electronic word, information communication life has already become a structure that functions static force balance between memory and personality; besides it operates the quantity and quality of information. Resolved with this study; the electronic word is an organic tool and activity of information-communication in a new World where the word gets effectiveness via technologization, where the interactive information flow is experienced. In the new nature of the electronization, human with changing literacy skills is reshaping himself/herself as an information collector-user.
Keywords: Technologization of the word; electronic word; the new World of information; the electronic age; the new literacy